ESTUDIO DEL ESTRÉS EN EL ÁMBITO ACADÉMICO PARA LA MEJORA DEL RENDIMIENTO ESTUDIANTIL - Gutiérrez Huby, Ana María (2016)
This article addresses the issue of academic stress as a problem that occurs on the student, which conditioned by its environment, limits the normal development in its studies. The purpose of the study is to provide an outreach to university authorities and teachers on this subject, which causes a number of psychological and physiological factors that impact on students’ performance. Among the points developed we will find a conceptual definition, historical evolu-tion, symptomatology, repercussions and the attitude that the university should take facing the presented situation, in order to contribute to the improvement of the academic success in students. The article con-cludes with the need to develop models and tools to objectively visualize the subject and propose relevant alternatives that contribute to the solution.